(NsEJSMOLOGI^ESKIE DONNYE NABL@DENIQ W sssr I ZA RUBEVOM (B/s - (NsOLOWXEW(B, (NsERGEJ lEONIDOWI^s; (NrYKUNOW(B,(Nl(B.(Nn(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 111-117s
(Nan sssr(B, (NmEVDUWED(B. (NSOWET PO SEJSMOLOGII I SEJSMOSTOJK(B. (NSTR(B-(NWUs
Keywords: (NsEJSMI^ESKIE NABL@DENIQ MORSKIEs